B Chronic oral tetrahydrobiopterin treatment in patients with coronary artery disease elevates total biopterin levels but does not improve biopterin redox status or vascular function: a randomised placebo-controlled trial. (22nd September 2015) - Cunnington, C; Van Assche, T; Shirodaria, C; Kylintireas, I; Lindsay, A C; Lee, J M S; Francis, J M; Sayeed, R; Ratnatunga, C; Pillai, R; Choudhury, R P; Neubauer, S; et al.
Abstract : Background: Tetrahydrobiopterin (BH4), a critical endothelial nitric oxide synthase (eNOS) cofactor, is an important determinant of endothelial function. Oral BH4 therapy has been proposed as a treatment for vascular disease. We investigated the pharmacokinetics and pharmacodynamics of oral BH4 in both plasma and vascular tissue to determine whether oral BH4 therapy would improve vascular function in patients with established atherosclerosis and oxidative stress. Methods: In a double-blind, randomised trial, 49 patients with coronary artery disease (CAD) awaiting coronary artery bypass graft surgery received oral BH4 700 mg/d (n=16) or 400 mg/d (n=14), or placebo (n=19), for a mean duration of 30 days prior to surgery. Biopterin levels were measured in plasma at baseline and after the treatment period, and in saphenous vein (SV) and internal mammary artery (IMA) tissue collected at the time of surgery. Vascular superoxide and endothelial function were measured ex vivo. Cardiovascular MRI was used to determine brachial artery flow-mediated dilatation and indices of arterial stiffness before and after treatment. Results: Plasma BH4 levels were elevated threefold by both low- and high-dose BH4 treatment compared to placebo (p<0.001), but levels of the oxidised biopterin species 7, 8-dihydrobiopterin (BH2), which lacks eNOS cofactor activity and may competitively inhibit BH4, were similarly elevated in plasma (p<0.001), such that BH4:BH2 ratio was unaffected. BH4 and BH2 were elevated twofold in SV tissue (p<0.001), but not significantly elevated in IMA (Abstract B figure 1 ), with no change in BH4:BH2 ratio in either vessel type. There was no difference in vascular superoxide or endothelial function ex vivo, or in MRI indices of vascular function. Conclusion: Although absolute BH4 levels in plasma and SV are increased, chronic oral BH4 therapy does not alter biopterin redox status (BH4:BH2 ratio) in either plasma or vascular tissue. Accordingly, oral BH4 does not improve vascular function or oxidative stress in patients with established CAD.